Endoscopic management of middle ear atelectasis - Marwa Shaaban Tawfik; Mohamed A Hussein; Mohamed M Elmoursy (Al-Azhar Assiut Medical Journal, 2021)
Objective To assess the efficacy of otoendoscopy in the surgical management of atelectatic ear to improve the clinical and the audiological outcomes. Patients and methods A total of 38 ears in 24 patients with middle ear atelectasis and intact ossicular chain were randomly assigned into two groups: group I (27 ears) underwent endoscopic T-tube insertion and group II (11 ears) underwent endoscopic cartilage tympanoplasty. Assessment of hearing was performed for all cases preoperatively and 3 months postoperatively. Results There is a significant postoperative improvement of air-bone gap averages reported in the two studied groups, with mean hearing gain of 21.67±7.97 dB in group I and 19.72±5.3 dB in group II. Conclusions At 3 months postoperatively, there was a significant statistical difference concerning different audiological parameters among the two groups.